Monetary policy regimes in CIS economies and their ability to provide price and financial stability - Marek Dabrowski (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
Achieving price stability has been a serious challenge for CIS countries. In the first half of the 1990s, they experienced very high inflation or hyperinflation, which had originated in the perestroika period and following the dissolution of the ruble area. After the introduction of new currencies and stabilization programs in the mid-1990s, inflation moderated to two-digit levels. However, for lack of sufficient fiscal policy support, this partial progress did not succeed in preventing the financial crisis of 1998/99. The economic boom of the 2000s allowed for a return to macroeconomic stability with stronger fiscal fundamentals, but nevertheless proved insufficient to withstand the shock from the global financial crisis of 2008/09. The paper analyses the evolution monetary policy regimes of in the CIS countries over the decade of the 2000s and early 2010s and is based on the publicly available cross-country statistics and other information provided by the IMF. The paper compares financial openness in these economies both de jure and de facto. These findings will be tested against the empirical data on exchange rate movements and changes in central banks' international reserves. The paper concludes with a discussion on practical choices which CIS countries have in respect of their future monetary policy regimes.
URN:NBN:fi:bof-201408072126
Keywords: E42; E58; P24; P52; 330; monetary policy; CIS; financial openness; inflation